Turning around the electron flow in an uptake hydrogenase. EPR spectroscopy and in vivo activity of a designed mutant in HupSL from Nostoc punctiforme. Issue 2 (15th December 2015) - Raleiras, Patrícia; Khanna, Namita; Miranda, Hélder; Mészáros, Lívia S.; Krassen, Henning; Ho, Felix; Battchikova, Natalia; Aro, Eva-Mari; Magnuson, Ann; Lindblad, Peter; Styring, Stenbjörn
Abstract : The uptake hydrogenase HupSL became a H2 producer in N. punctiforme after modifying the proximal FeS cluster with the single point mutation C12P. Abstract : The filamentous cyanobacterium Nostoc punctiforme ATCC 29133 produces hydrogen via nitrogenase in heterocysts upon onset of nitrogen-fixing conditions. N. punctiforme expresses concomitantly the uptake hydrogenase HupSL, which oxidizes hydrogen in an effort to recover some of the reducing power used up by nitrogenase. Eliminating uptake activity has been employed as a strategy for net hydrogen production in N. punctiforme (Lindberg et al., Int. J. Hydrogen Energy, 2002, 27, 1291–1296). However, nitrogenase activity wanes within a few days. In the present work, we modify the proximal iron-sulfur cluster in the hydrogenase small subunit HupS by introducing the designed mutation C12P in the fusion protein f-HupS for expression in E. coli (Raleiras et al., J. Biol. Chem., 2013, 288, 18345–18352), and in the full HupSL enzyme for expression in N. punctiforme . C12P f-HupS was investigated by EPR spectroscopy and found to form a new paramagnetic species at the proximal cluster site consistent with a [4Fe–4S] to [3Fe–4S] cluster conversion. The new cluster has the features of an unprecedented mixed-coordination [3Fe–4S] metal center. The mutation was found to produce stable protein in vitro, in silico and in vivo . When C12P HupSL was expressed in N. punctiforme, the strain had a consistently higher hydrogen production than the background Δ hupSL mutant. We conclude that the increase in hydrogen production is due to the modification of the proximal iron-sulfur cluster in HupS, leading to a turn of the electron flow in the enzyme.